Seroprevalence of hypodermosis in cattle in some provinces of Turkey - Simsek, Sami; Utuk, Armagan Erdem; Koroglu, Ergun; Dumanli, Nazir (Elsevier Sci Ltd, 2008)
The aim of this study was to determine the seroprevalence of hypodermosis in cattle in the east and southeast of Turkey. For this purpose, a total of 634 sera samples of cattle were collected from Malatya, Elazig and Diyarbakir provinces of east and southeast of Turkey from November 2005 to February 2006. The sera were analyzed using a Hypodermin C antigen by means of indirect ELISA. One hundred and forty eight (23.3%) out of 634 cattle were seropositive for hypoderma antibodies. The highest percentage of seropositivity were detected at Elazig province (26.3%) followed by Malatya (22.3%) and Diyarbakir provinces (22.1%). The seropositivity rate was higher in female (31%) than male (14.1%). When the mean is considered by animal breed, the highest seropositivity was detected at local breed (27.7%) following crossbreed (26.8%) and purebreed (19.7%). There was a positive relation between age and seropositivity. Seropositivity rate was 15.9% in 2 and under ages while these rates were 38.1% and 30.4% in 3-4 ages and 5 and up ages, respectively. (c) 2007 Eisevier Ltd. All rights reserved.
Keywords: hypodermosis; cattle; ELISA; prevalence; Turkey